IMPLIKASI AMANDEMEN UNDANG-UNDANG TENTANG ZAKAT TERHADAP OPTIMALISASI PENGUMPULAN DAN PEMBERDAYAAN ZAKAT - Yusep Rafiqi (JURNAL EKONOMI SYARIAH, 2019)
Zakat is maaliyah ijtima'iyyah worship, it means worship in the area of property that has a very important position in the development of society. Zakat is purification treasure for muzakki and develop the economy for mustahik. Thus, zakat can contain two effects at once; spiritual impact and economic impact. The impact of issuing this treasure should be able to motivate muzaki to continuously purify the treasures with regular charity which, in turn, have a direct impact on the level of welfare of the mustahik. However, in reality, poverty is still notmoved. During this time, the government's efforts to reduce poverty are many initiated and pursued to be realized. Among others, by formulating standards and draw up a map of poverty pockets of poverty. By looking at the reality of poverty, tackling problems and solutions offered Islam, required laws that defend the rights of the poor and poverty reduction procedure itself. In the context of the laws of the Republic of Indonesia, the government's efforts to accommodatethe interests of Muslims and efforts to eradicate poverty is by enacting two laws product zakat management. Legislation in question is Act No. 38 of 1999 and Act No. 23 of 2011 on the management of zakat. However, the legislation needs to be reassessed its effectiveness because until today the empowerment of zakat is still far from expectations